Topical Drug Delivery: Innovative Controlled Release Systems - Daniele Ribeiro de Araujo; Cristina Padula (MDPI AG, 2023)
One of the most innovative strategies for administrating bioactive molecules is the design of adequate drug delivery systems [...]